Impact of practice teaching on student-teachers teaching skills: A study from Abu Dhabi, United Arab Emirates’ A Study conducted in a Higher Education Institute level in the UAE - ALMANSOORI, AFRA GHAREEB AHMED MOHAMMED (2017)
Lack of teaching experience can affect the new teachers seriously and reduce their productivity. The purpose of this research is discovering the relationship between teaching practice and the student-teachers professional growth from the staff and students perspectives. The main research question is ‘What is the impact of ongoing teaching practice on student-teachers professional development? The secondary questions are, what is the best practice in practice teaching suggested by student-teachers and staff? How can student-teachers and staff get the most of the practice teaching and expand their knowledge? And has ongoing teaching practice been effective? Why?. The objectives of this research is to identify the effectiveness of teaching practice on student-teachers and staff performance. To establish a criteria for the best practice in teaching recommended by student-teachers and staff. To describe to what extent and this teaching practice has been effective. Key theories were explored in this research for instance, Bloom’s Taxonomy theory, craft of inquiry which is learning through observation, micro teaching, and model of teaching. Mixed methods of approach were used to gather the information, quantitative and qualitative. The survey was used as a quantitative tool. It was designed for student-teachers only and they were 121 students. The questionnaire was used a quantitative approach. The number of faculty who were involved in this study was 8 female lecturers. Key findings of this study are the following, Teaching practice affects the student-teachers performance positively. Teaching practice affects the staff as well and enable them to give appropriate feedback. Teaching practice improves the student-teachers and staff in three different domains, psychology, philosophy, and socially. The study concluded with the huge difference of teaching practice in student-teachers teaching and learning skills.